Analisis Sistem Distribusi BBM Dengan Menggunakan Konsep Cost-Based Value Stream Mapping di PT. Pertamina - ., Derlini; Purwanto, Hadi; Polewangi, Yudi Daeng; Silvana, Nukhe Andri; Herlambang, Andri (Fakultas Teknik UMSU, 2023)
PT. Pertamina (Persero) Marketing Operation Region 1 (MOR1) oil fuel Terminal (TBBM) Medan Group has a problem that is less optimized the cost of the company's operational activities so as to reduce the company's profit then in this research combine the concept of cost-based and value stream mapping by describing the flow of information and material on the value stream and continued by calculating the cost based. After the calculation of the results can be obtained before the cost reduction, then the company to run its operational activities that consist of the process of acceptanming its duties and responsibilities as a distribution of fuel so that the operational activities of the company issued a distribution fee of Rp. 3.964,- / liter, then from the supply point switching there are 68 industrial companies that can be transferred to the fuel Terminal Pematangsiantar and 34 diverted to the fuel Terminal range so that the company can reduce the cost of distribution fuel by Rp. 2.429,-/liter.ce, filling and distribution of fuel to issue a distribution fee of Rp. 6.393,-/liter, by describing the value stream of identification of some waste namely waste waiting, waste over processing, waste motions and waste of transportation. After the improvement is the reduction of waste and supply point transfer to several industrial companies, the company can create effectively and efficiently in perfor.